Comparative Study on the Elucidation of Sedimentary Phosphorus Species Using Two Methods, the SMT and SEDEX Methods - Pei Sun Loh; Chen-Yu Ying; Hussien Ibrahim Mohammed Alnoor; Xing-Rui Huang; Zhang-Hua Lou; Xue-Gang Chen; Shuangyan He; Zong-Pei Jiang; Ai-Min Jin (Journal of Analytical Methods in Chemistry)
Sedimentary phosphorus (P) forms are important representatives of P sources and their bioavailability as well as the potential of sediments to release P in water. In this study, surface sediments along a transect of the Changjiang Estuary and two transects along the Andong salt marsh in the southwest of Hangzhou Bay were subjected to the elucidation of sedimentary P species using the standards, measurements, and testing (SMT) and sequential extraction (SEDEX) methods. The results showed that the mean sedimentary P forms elucidated by the SMT method were as follows: organic P (OP; ∼11–14 mg/kg; ∼30–45% of total P; TP) > apatite P (∼5–15 mg/kg; ∼21–36% TP) > Fe/Al-P (∼8–14 mg/kg; ∼31–34% TP), with inorganic P (IP) composing 54–70% of TP. The mean sedimentary P forms elucidated by the SEDEX method were as follows: authigenic P (∼54–68 mg/kg; ∼41–46% TP) > extractable P (Ex-P; ∼36–53 mg/kg; ∼28–34%) > Fe-P (∼21–27 mg/kg; ∼13–19%) > OP (∼8.7–13 mg/kg; ∼5–8%) > detrital P (De-P; ∼2 mg/kg; ∼1–2% TP), with IP composed of ∼91–94% TP. These results showed that the SEDEX method elucidated higher concentrations of sedimentary P forms as well as the TP from these coastal sediments although the SMT method had the advantage of being more economic and faster. The results of both the SMT and SEDEX methods showed that the Andong salt marsh and Changjiang Estuary sediments had much bioavailable P. The mean percentages of bioavailable P from the SMT and SEDEX methods were ∼64–74% and 52–56% of TP, respectively, indicating that these sediments were prone to release P to the coastal areas.